Chorion and amnion/chorion membranes in oral and periodontal surgery: A systematic review. Issue 8 (22nd December 2020) - Gulameabasse, Sarah; Gindraux, Florelle; Catros, Sylvain; Fricain, Jean‐Christophe; Fenelon, Mathilde
Abstract: The aim of this study was to perform a systematic review on the clinical applications where chorion membrane (CM) and amnion/chorion membrane (ACM) were used for oral tissue regeneration procedures. Selection of articles was carried out by two evaluators in Pubmed and Scopus databases, and Outcomes (PICO) method was used to select the relevant articles. Clinical studies reporting the use of CM or ACM for oral soft and hard tissue regeneration were included. The research involved 21 studies conducted on 375 human patients. Seven clinical applications of CM and ACM in oral and periodontal surgery were identified: gingival recession treatment, intrabony and furcation defect treatment, alveolar ridge preservation, keratinized gum width augmentation around dental implants, maxillary sinus membrane repair, and large bone defect reconstruction. CM and ACM were compared to negative controls (conventional surgeries without membrane) or to the following materials: collagen membranes, dense polytetrafluoroethylene membranes, platelet‐rich fibrin membranes, amnion membranes, and to a bone substitute. Several studies support the use of CM and ACM as an efficient alternative to current techniques for periodontal and oral soft tissue regeneration procedures. However, further studies are necessary to increase the level of evidence and especially to demonstrate their role for bone regeneration.